Ethnic groups' knowledge, attitude and practices and Rift Valley fever exposure in Isiolo County of Kenya. - Hippolyte Affognon; Peter Mburu; Osama Ahmed Hassan; Sarah Kingori; Clas Ahlm; Rosemary Sang; Magnus Evander (Public Library of Science (PLoS), 2017)
Rift Valley fever (RVF) is an emerging mosquito-borne viral hemorrhagic fever in Africa and the Arabian Peninsula, affecting humans and livestock. For spread of infectious diseases, including RVF, knowledge, attitude and practices play an important role, and the understanding of the influence of behavior is crucial to improve prevention and control efforts. The objective of the study was to assess RVF exposure, in a multiethnic region in Kenya known to experience RVF outbreaks, from the behavior perspective. We investigated how communities in Isiolo County, Kenya were affected, in relation to their knowledge, attitude and practices, by the RVF outbreak of 2006/2007. A cross-sectional study was conducted involving 698 households selected randomly from three different ethnic communities. Data were collected using a structured questionnaire regarding knowledge, attitudes and practices that could affect the spread of RVF. In addition, information was collected from the communities regarding the number of humans and livestock affected during the RVF outbreak. This study found that better knowledge about a specific disease does not always translate to better practices to avoid exposure to the disease. However, the high knowledge, attitude and practice score measured as a single index of the Maasai community may explain why they were less affected, compared to other investigated communities (Borana and Turkana), by RVF during the 2006/2007 outbreak. We conclude that RVF exposure in Isiolo County, Kenya during the outbreak was likely determined by the behavioral differences of different resident community groups. We then recommend that strategies to combat RVF should take into consideration behavioral differences among communities.